Playing war wargaming and U.S. Navy preparations for World War II - Lillard, John M. 1958- (Potomac Books, an imprint of the University of Nebraska Press, 2016)
Between the First and the Second World War, the US Navy used theexperience it had gained in battle to prepare for future wars through simulated conflicts at the Naval War College. John M. Lillard analyses individual war games in detail, showing how players tested new tactics and doctrines, experimented with advanced technology, and transformed approaches